1984
DOI: 10.1083/jcb.99.3.1101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microtubule assembly status on the intracellular processing and surface expression of an integral protein of the plasma membrane.

Abstract: We studied the effects of changes in microtubule assembly status upon the intracellular transport of an integral membrane protein from the rough endoplasmic reticulum to the plasma membrane. The protein was the G glycoprotein of vesicular stomatitis virus in cells infected with the Orsay-45 temperature-sensitive mutant of the virus; the synchronous intracellular transport of the G protein could be initiated by a temperature shift-down protocol. The intracellular and surface-expressed G protein were separately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
108
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(125 citation statements)
references
References 37 publications
17
108
0
Order By: Relevance
“…Certain models of cell locomotion involve the addition of new membrane at the leading edge (for review see Singer and Kupfer, 1986); this edge was reported to be the primary site of microtubule-dependent incorporation of membrane marker protein (Bergmann et al, 1983;Rogalski et al, 1984). HD injections could probably stop this membrane addition and thus suppress pseudopodial activity and cell locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…Certain models of cell locomotion involve the addition of new membrane at the leading edge (for review see Singer and Kupfer, 1986); this edge was reported to be the primary site of microtubule-dependent incorporation of membrane marker protein (Bergmann et al, 1983;Rogalski et al, 1984). HD injections could probably stop this membrane addition and thus suppress pseudopodial activity and cell locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…The situation that exists for membrane protein transport, however, appears to be different. The rate and extent of VSV G protein surface expression in virusinfected fibroblasts is not altered due to microtubular disruption (Rogalski et al, 1984), and conflicting reports of the effect of these agents on the polarity of viral protein transport exist. Rogalski et al (1984) suggested that the polarity of VSV G protein surface expression is altered because of microtubular disruption.…”
Section: Discussionmentioning
confidence: 99%
“…The rate and extent of VSV G protein surface expression in virusinfected fibroblasts is not altered due to microtubular disruption (Rogalski et al, 1984), and conflicting reports of the effect of these agents on the polarity of viral protein transport exist. Rogalski et al (1984) suggested that the polarity of VSV G protein surface expression is altered because of microtubular disruption. Rindler et al (1987) observed no alteration in polarity of VSV G protein surface expression with microtubular disruption, but did observe altered polarity of influenza hemagglutinin surface expression.…”
Section: Discussionmentioning
confidence: 99%
“…4C, a and b). We further examined the relationship between CG-NAP and the Golgi apparatus using the microtubule-destabilizing agent nocodazole (27) and the fungal metabolite BFA (28), which are known to disrupt the Golgi apparatus by distinct mechanisms. Nocodazole treatment of HeLa cells dispersed the perinuclear CG-NAP staining into scattered pattern throughout the cytoplasm (Fig.…”
Section: Yeast Two-hybrid Screen For Pkn Interacting Proteins-thementioning
confidence: 99%